Existence and Uniqueness of Solutions to Third-Order Boundary Value Problems - Almuthaybiri, S. S.; Jonnalagadda, J. M.; Tisdell, C. C. (Trends in Computational and Applied Mathematics, 2021)
The purpose of this research is to connect fixed point methods with certain third-order boundary value problems in new and interesting ways. Our strategy involves an analysis of the problem under consideration within closed and bounded sets. We develop sufficient conditions under which the associated mappings will be contractive and invariant in these sets, which generates new advances concerning the existence, uniqueness and approximation of solutions.